Achieving strong friction lap joints of carbon-fiber reinforced plastic and metals by modifying metal surface structure via laser-processing pretreatment. (15th June 2020) - Wu, L.H.; Xiao, B.L.; Nagatsuka, K.; Nakata, K.; Ma, Z.Y.
Graphical abstract: Highlights: Porous metal surface structures are benefit for strengthening metal-CFRP joints. Laser processing pretreatment strengthened metal-CFRP friction lap joints by twice. The laser processed Al-CFRP joint showed 4.9 kN in TSF and 78% in joint efficiency. The strength increase was due to the mechanical anchor and chemical bond increase. This study provides a new surface treatment way to strengthen metal-CFRP joints. Abstract: Strong dissimilar joints of metals and carbon fiber reinforced plastic (CFRP) are highly demanded for the lightweight design in many fields, which, however, are rather challenging to achieve directly via welding. In this study, 5052 Al alloy and plain carbon steel were first pretreated by a laser-processing method to create rather coarse porous metal surfaces, which were then welded to polyamide 6 based CFRP using friction lap joining. The maximum tensile shear force of the dissimilar joints of CFRP-Al alloy and CFRP-steel achieved 4.9 kN, and 3.9 kN, respectively, and the joint efficiency achieved 78% and 62%, respectively, which were more than three times as those of the CFRP- as-received metal joints. This is the first report on the strengthening of the metal-CFRP friction based joints via the assisting laser treatment technique. The significant improvement of the joint strength could be attributed to a great increase of the mechanical anchors and the chemical bonding area at the metal-CFRP interface.